A tutela penal da ordem tributária: a inconstitucionalidade do tratamento dado ao sonegador - Albuquerque, Eduardo Garcia (2023)
The complexity of the Brazilian tax collection system opens a discussion about the need (or not) to criminalize conduct that, through illegitimate artifices, reduce or suppress the amounts to be collected by state entities. In this context, several normative instruments, with the complacency of the Judiciary, have transformed the Tax Criminal Law into another instrument of coercion that aims to "stimulate" the tax evader to pay his debts. The penalty ceases to have a pedagogical and resocializing character and becomes a collection tool. This new view of tax crimes generates numerous inconsistencies in the Brazilian legal system, especially when confronted with the system applicable to other property crimes, whose agents are not rewarded by the benefits to which the tax evader is entitled. The present work aims at an in-depth analysis of this "evolution", in my view distorted, of Tax Criminal Law, from the perspective of the legal good that is intended to be protected. Based on the constitutional principles applicable to criminal law, an approach was made to the understanding established in the scope of the Superior Courts about tax crimes, pointing out what would be the mistakes observed. Finally, there is a special approach to the instrument of extinction of punishability by the full payment of the tax debt, with the necessary criticisms, including bringing to the discussion the analogous instruments existing in comparative law.